Integrated process for the production of lipase and methane from olive mill wastewaters - Gonçalves, Cristiana (2010)
The continuous system for olive oil production can be operated by three and two-phase extraction technologies, diverging in the water supplies. The three-phase extraction process has a slightly better yield, leading to less amount of olive cake but a significant production of olive mill wastewater (OMW). The aim of the present work is the OMW valorization by producing high-value compounds while degrading this waste. The effluents are submitted to a lipase producing aerobic fermentation that contributes for a partial OMW degradation, followed by an anaerobic methanogenic degradation process. The aerobic treatment, with production of lipase, is useful for a better yield of methane production. The lipase produced on the aerobic step had loss some activity from 60% to 95%. Best results were achieved for 5 g OMW COD L-1 in terms of methane production (78% of methanisation) and lipase activity decay (60%).